2015
DOI: 10.1007/s10549-015-3516-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of protein tyrosine phosphatase, non-receptor type 2 is associated with activation of AKT and tamoxifen resistance in breast cancer

Abstract: Gene copy loss of PTPN2 was detected in 16% (34/215) of the tumours and this was significantly correlated with lower levels of PTPN2 mRNA. PTPN2 gene loss and lower mRNA levels were associated with activation of AKT and a poor prognosis. Furthermore, PTPN2 gene loss was a significant predictive marker of poor benefit from tamoxifen treatment.In conclusion, genomic loss of PTPN2 may be a previously unknown mechanism of PI3K/AKT upregulation in breast cancer. PTPN2 status is a potential new clinical marker of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
4
27
1
Order By: Relevance
“…TAM is widely used for treating ER-positive BCs, but its side effects and the gradual development of insensitivity limit its effectiveness. Many studies have shown that resistance to TAM is partly mediated through the AKT pathway, which promotes estrogen-independent cell proliferation [ 20 ]. The AKT pathway also plays a crucial role in breast cancer pathogenesis, and AKT upregulation is associated with more aggressive clinical phenotypes and worse outcomes in endocrine-treated patients [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAM is widely used for treating ER-positive BCs, but its side effects and the gradual development of insensitivity limit its effectiveness. Many studies have shown that resistance to TAM is partly mediated through the AKT pathway, which promotes estrogen-independent cell proliferation [ 20 ]. The AKT pathway also plays a crucial role in breast cancer pathogenesis, and AKT upregulation is associated with more aggressive clinical phenotypes and worse outcomes in endocrine-treated patients [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapies, such as tamoxifen and trastuzumab, have improved the outcomes of patients with ER + or HER2 + breast cancer (3,4). However, a number of patients with breast cancer exhibit de novo or acquired target therapy resistance (5,6). In addition, chemotherapy is the only treatment option for patients with triple-negative breast cancer (TNBC; ER -/HER2 -/PR -) and targets for the effective treatment remain to be elucidated (7).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the phosphatidyl-inositol-3 kinase pathway as measured by phosphorylation status of components of the protein cascade has been shown to correlate with tamoxifen resistance, while this was not found for its upstream drivers like the presence of a PIK3CA hotspot mutation, or PTEN loss [ 29 , 30 ]. AKT inhibitors have been shown to extend the duration of response to both tamoxifen and AI in pre-clinical models [ 31 ].…”
Section: Discussionmentioning
confidence: 99%